The origins of hospital culture. Solidarity in the work in hospital is medicine for man - Brera, Giuseppe R. (Medicina e Morale, 1986)
Hospital solidarity is born, develops and ends in love, or at least that is how it should be. It is a strange love, the one that brings Hospitals to life, perhaps paradoxical and anachronistic if one wants to generalise in a rather superficial way, because it finds its object and subject in pain and suffering. It seems illogical that Hospitals can find their meaning in pain and suffering, it seems so far from 'common sense' that pain and suffering can generate and not remain occasional and final episodes of random and indeterminate existences.